Diagnostic management of occult nodal lymphangioleiomyomatosis detected during pelvic cancer staging. Localized finding or systemic disease? - Remo, Andrea; Zanella, Caterina; Parcesepe, Pietro; Greco, Filippo; Pancione, Massimo; Zapparoli, Mara Maria; Manfrin, Erminia; Micheletto, Claudio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: Lymphangioleiomyomatosis (LAM) is a neoplastic disease that generally arises in the lung (pLAM) and may be associated with “Tuberous sclerosis complex” (TSC). Occasionally, LAM can arise at the extrapulmonary sites (eLAM), such as the mediastinum, the retroperitoneum or the lymph nodes. 25-30% of the patients affected by pLAM develop eLAM. In asymptomatic patients, the presence of mediastinal and retroperitoneal eLAM preceded that of pLAM by usually 1-2 years. Nevertheless, some authors reported that the nodal eLAM, detected during pelvic cancer staging, arise in patents without pLAM and/or TSC. In this paper we review the Literature of this rare condition suggesting its diagnostic management. Results: To date, it has been reported 30 cases. The mean age at diagnosis is 55 years and around  30% of patients are postmenopausal. In only 2 cases was diagnosed a following p-LAM. One patient with endometrioid carcinoma and pelvic nodal eLAM reported TSC2 germiline mutation. None case was associated with both p-LAM and TSC. Conclusions: The retrospective probability to have p-LAM in patients with staging pelvic nodal e-LAM is 6,6% (4/30) lower than the probability to have e-LAM in patients affected by p-LAM (25-30%). In both this association is more probable sporadically than associated with TSC. The association between cancer staging pelvic nodal e-LAM and TSC is low (3%; 1/30). The p-LAM developed are asymptomatic with a behavior, regardless of hormonal status, similar to lesions diagnosed in postmenopausal although further studies are mandatory to confirm it.